Adaptive $2×2$ MIMO Employed Wavelet-OFDM-Radio Over Fibre Transmission - Vishal Sharma; Sergey Sergeyev; Jaswinder Kaur (IEEE Access, 2020)
Due to high peak-to-average-power ratio (PAPR) and low spectral-efficiency, the conventional Fast Fourier Transform based orthogonal frequency division multiplexing (OFDM) is losing its place to the other multicarrier modulation schemes. Alternatively, the wavelet treated multiple-input multiple-output (MIMO)-OFDM is gaining its popularity in realization of futuristic 5G networks due to proffering high spectral-efficiency, low-cost and low phase-noise. Subsequently, this work demonstrates a RF transmission system in S-band employing 2×2 MIMO-OFDM using orthogonaland biorthogonal-wavelets with diverse phase shift keying modulation (PSK) schemes. Among the available MIMO configurations, the authors implement spatial diversity as it promises good reliability in noisy links [11]. However, the distribution of Wavelet-OFDM (W-OFDM) signals over a radio over fibre (RoF) link is critically affected by the optical sub-system non-linearity. So, the simplest 2×2 Alamouti's space-time block code (STBC) is implemented in this work to overcome this non-linearity and to realize a less-complex detection. The work is further extended to realize an adaptive MIMO-RoF system employing W-OFDM scheme to adjust itself to a suitable available phase shift keying strategy as per the link-situation to retain an optimal balance of link-quality and spectral-efficiency.